2019
DOI: 10.1063/1.5091736
|View full text |Cite
|
Sign up to set email alerts
|

Towards surface diffusion potential mapping on atomic length scale

Abstract: The surface diffusion potential landscape plays an essential role in a number of physical and chemical processes such as self-assembly and catalysis. Diffusion energy barriers can be calculated theoretically for simple systems, but there is currently no experimental technique to systematically measure them on the relevant atomic length scale. Here, we introduce an atomic force microscopy based method to semi-quantitatively map the surface diffusion potential on an atomic length scale. In this proof of concept … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…1 A. The structure and growth mode of metal chains on Si(100) has previously been well studied by scanning probe methods, and both STM [36][37][38][39] and NC-AFM [3,19,20] studies have shown that at low coverages many metal species self-assemble into chains which nucleate at a surface defect or step edge and grow perpendicular to the direction of the Si rows in dimer units. For Pb specifically, it is thought that chains terminated by a single Pb at the end of the chain are energetically favourable [35,38].…”
Section: A Comparison Of Stm and Nc-afm Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A. The structure and growth mode of metal chains on Si(100) has previously been well studied by scanning probe methods, and both STM [36][37][38][39] and NC-AFM [3,19,20] studies have shown that at low coverages many metal species self-assemble into chains which nucleate at a surface defect or step edge and grow perpendicular to the direction of the Si rows in dimer units. For Pb specifically, it is thought that chains terminated by a single Pb at the end of the chain are energetically favourable [35,38].…”
Section: A Comparison Of Stm and Nc-afm Imagingmentioning
confidence: 99%
“…Despite its greater technological relevance, the imaging of adsorbates on the Si(100) surface remains less explored by NC-AFM imaging. Notable exceptions are the identification of the structural and chemical identity of mixed adatom chains via combined NC-AFM and STM [3], imaging and manipulation of both Sn [19], and Mn adatom chains [20] [21], and characterisation of intrinsic boron defects [22]. However, in none of these studies was the interaction of different types of scanning probe tip with the absorbed structures investigated in detail, nor was the range, and limitations, of the manipulation processes.…”
Section: Introductionmentioning
confidence: 99%